Book Reviews. Issue 1 (1st March 2021) - Unknown
Abstract : Darryl Li, The Universal Enemy: Jihad, Empire, and the Challenge of Solidarity . Stanford University Press, pp. 364, 2020. Hannah Knox, Thinking Like a Climate: Governing a City in Times of Environmental Change . Durham, NC: Duke University Press, pp. 328, 2020.